2014
DOI: 10.1080/19476337.2014.963147
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pea products on the functional properties of frankfurters

Abstract: The aim of this study was to compare the functional properties of two pea products -the commercial product PeaTex and lyophilized peas and to determine their effects on the quality of frankfurters. Pea products differed in the composition of their protein fractions -PeaTex had a lower albumin content. Lyophilized peas were characterized by a better water-binding capacity at ambient temperature (1.62 ml/g). The highest emulsification capacity was observed for PeaTex (57.8%) at a NaCl concentration of 40 g/kg. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…This result could be linked to the fat and moisture retention within the tridimensional matrix of these polysaccharides. Other studies have also reported similar observations when FB was included in British style fresh sausage, 27 beef burgers 28 and bologna 5 as well as when CF was used as fat replacer in LF beef burger 29 and when PF was used in frankfurter 30 . Except for CF having higher cooking loss than ST, there were no significant differences ( P > 0.05) in cook yield among the LF formulations with the inclusion of the pulse ingredients (Table 3).…”
Section: Resultssupporting
confidence: 65%
“…This result could be linked to the fat and moisture retention within the tridimensional matrix of these polysaccharides. Other studies have also reported similar observations when FB was included in British style fresh sausage, 27 beef burgers 28 and bologna 5 as well as when CF was used as fat replacer in LF beef burger 29 and when PF was used in frankfurter 30 . Except for CF having higher cooking loss than ST, there were no significant differences ( P > 0.05) in cook yield among the LF formulations with the inclusion of the pulse ingredients (Table 3).…”
Section: Resultssupporting
confidence: 65%
“…This decrease is consistent with the production of lactic acid by lactic acid bacteria during the processing of fermented meat products [ 23 ]. From the 14th day, there was an increase in pH, probably due to proteolytic reactions, which produce nitrogenous compounds that can increase pH [ 24 , 25 ]. The pH evolution in this study follows the standard dynamics reported in the literature for this type of meat product [ 23 , 24 , 26 ], suggesting that the reformulation did not adversely affect this parameter.…”
Section: Resultsmentioning
confidence: 99%
“…tenebrionis (BGSC 4AA1) served as controls in PCR reactions. Bacillus thuringiensis strains were screened for lepidopteran-specific cry and vip genes ( cry 1, cry 2, cry 9 and vip 3A), Coleopteran-specific cry genes ( cry 3, cry 7 and cry 8), and Dipteran-specific cry and cyt genes ( cry 4, cry 10, cry 11, cyt 1 and cyt 2), using universal and gene specific primers (Ben-Dov et al, 1997; Ben-Dov et al, 1999; Bravo et al, 1998; Ejiofor & Johnson, 2002; Porcar & Juárez-Pérez, 2003). Each amplification reaction (25 µL) contained 200 µM dNTP, 0.5 µM of each primer, 2.5 mM MgCl 2 , and 2.5 U of Taq DNA polymerase.…”
Section: Methodsmentioning
confidence: 99%